An Adaptogen: Withaferin A Ameliorates in Vitro and in Vivo Pulmonary Fibrosis by Modulating the Interplay of Fibrotic, Matricelluar Proteins, and Cytokines - Bale, Swarna; Venkatesh, Pooladanda; Sunkoju, Manoj; Godugu, Chandraiah (Frontiers in Pharmacology, 2018)
Pulmonary fibrosis is chronic lung disease with only two FDA approved clinically available drugs, with limited safety profile. Inadequate therapy motivated us to explore the effect of vimentin inhibitor Withaferin A, as an anti-fibrotic agent against TGF-β1-induced in vitro fibrotic events and Bleomycin induced in vivo fibrosis with an emphasis on epithelial to mesenchymal transition (EMT), extracellular matrix deposition (ECM), inflammation and angiogenesis. In vitro EMT and fibrotic events were induced by TGF-β1 in alveolar epithelial cells and human fetal lung fibroblasts followed by treatment with Withaferin A (0.25, 0.5 and 1 µM concentrations) to explore its anti-fibrotic effects. In vivo potential of Withaferin A (2 and 4 mg/kg) was assessed in murine model of Bleomycin induced pulmonary fibrosis. All the parameters and molecular studies related to pulmonary fibrosis were performed at the end of treatment period. Withaferin A treatment reduced the progression of pulmonary fibrosis by modulating the EMT related cell markers both in vivo and in vitro. Withaferin A ameliorated the expression of inflammatory cytokines including NF-κB, IL-1β and TNF-α, as well as attenuated the expression of pro-fibrotic proteins including CTGF, Collagen 1A2, Collagen 3A1 and fibronectin. Expression of angiogenic factors like VEGF, FAK, p38 MAPK and PLC-γ1 were also inhibited by Withaferin A. Phosphorylation of Smad 2/3 induced by TGF-β1 and Bleomycin were significantly inhibited. Withaferin A suppressed expression of pro-inflammatory, pro-fibrotic and pro-angiogenic mediators and also reduced the ECM deposition. In a nutshell, Withaferin A could probably prove as an efficient and potential therapeutic against pulmonary fibrosis.